Impact of Alkyl Side Chains on Optoelectronic and Photovoltaic Properties of Novel Benzodithiophenedione‐Based Conjugated Polymers. Issue 9 (24th May 2019) - Akkuratov, Alexander; Martinov, Ilya; Avilova, Irina; Troshin, Pavel
Abstract : Two novel donor–acceptor conjugated polymers comprising benzo[1, 2‐ c :4, 5‐ c ′]dithiophene‐4, 8‐dione and an extended TTBTBTT system (thiophene—T, benzothiadiazole—B) with different alkyl side chains are synthesized and investigated. It is found that the length of alkyl side chains has a strong influence on energy levels, film morphology, and charge‐carrier mobility of the designed polymers. Organic solar cells based on polymer P2 with bulky 2‐hexyldecyl side chains demonstrate significantly improved photovoltaic performances as compared to the devices based on P1 bearing relatively small 2‐ethylhexyl solubilizing groups. Abstract : Two novel (X‐DADAD) n ‐type conjugated polymers (D and A represent thiophene and benzothiadiazole units, respectively) comprising benzodithiophenedione building block X reveal a remarkable effect of alkyl side chains on their physicochemical, rheological, optoelectronic, and photovoltaic properties. Optimal side chains result in the fivefold increase in the efficiency of organic solar cells, reaching a promising value of 6.8% using a fullerene acceptor [70]PCBM ([6, 6]‐phenyl‐C71 ‐butyric acid methyl ester).